The rule is exponential function.
Answer:
Step-by-step explanation:
1 In general, given a{x}^{2}+bx+cax
2
+bx+c, the factored form is:
a(x-\frac{-b+\sqrt{{b}^{2}-4ac}}{2a})(x-\frac{-b-\sqrt{{b}^{2}-4ac}}{2a
2a
−b+√
b
2
−4ac
)(x−
2a
−b−√
b
2
−4ac
)
2 In this case, a=1a=1, b=-2b=−2 and c=-2c=−2.
(x-\frac{2+\sqrt{{(-2)}^{2}-4\times -2}}{2})(x-\frac{2-\sqrt{{(-2)}^{2}-4\times -2}}{2})(x−
2
2+√
(−2)
2
−4×−2
)(x−
2
2−√
(−2)
2
−4×−2
)
3 Simplify.
(x-\frac{2+2\sqrt{3}}{2})(x-\frac{2-2\sqrt{3}}{2})(x−
2
2+2√
3
)(x−
2
2−2√
3
)
4 Factor out the common term 22.
(x-\frac{2(1+\sqrt{3})}{2})(x-\frac{2-2\sqrt{3}}{2})(x−
2
2(1+√
3
)
)(x−
2
2−2√
3
)
5 Cancel 22.
(x-(1+\sqrt{3}))(x-\frac{2-2\sqrt{3}}{2})(x−(1+√
3
))(x−
2
2−2√
3
)
6 Simplify brackets.
(x-1-\sqrt{3})(x-\frac{2-2\sqrt{3}}{2})(x−1−√
3
)(x−
2
2−2√
3
)
7 Factor out the common term 22.
(x-1-\sqrt{3})(x-\frac{2(1-\sqrt{3})}{2})(x−1−√
3
)(x−
2
2(1−√
3
)
)
8 Cancel 22.
(x-1-\sqrt{3})(x-(1-\sqrt{3}))(x−1−√
3
)(x−(1−√
3
))
9 Simplify brackets.
(x-1-\sqrt{3})(x-1+\sqrt{3})(x−1−√
3
)(x−1+√
3
)
The answer is 29
29 is the answer because:
Following PEMDAS
5*6=30
3+30=33
33-4=29
Answer:
Scatter plot with line of best fit of y equals 0.75x plus five.
The line of best fit is y = 0.75x + 5.
Choose the best representation for the slope.
The slope of the line of best fit shows that each additional minute, the distance increases by 0.75 feet.
The slope of the line of best fit shows that each additional minute, the distance decreases by 5 feet.
The slope of the line of best fit shows that each additional minute, the distance decreases by 0.75 feet.
The slope of the line of best fit shows that each additional minute, the distance increases by 5 feet.
Answer:
<h2>X = 66°</h2>
<u>Step-by-step explanation:</u>
ΔH + ΔJ + ΔK + ΔG = 360°
103° + 133° + 58° + X = 360°
294° + X = 360°
X = 360° - 294°
X = 66°